Photoinduced homolytic C–H activation in N-(4-homoadamantyl)phthalimide - Cindro, Nikola; Horvat, Margareta; Mlinarić-Majerski, Kata; Griesbeck, Axel G.; Basarić, Nikola (Beilstein Journal of Organic Chemistry, 2011)
N-(4-homoadamantyl)phthalimide (5) on excitation and population of the triplet excited state underwent intramolecular H-abstractions and gave products 6 and 7. The major product, exo-alcohol 6 was a result of the regioselective δ H-abstraction and the stereoselective cyclization of the 1,5-biradical. Minor products 7 were formed by photoinduced γ H-abstractions, followed by ring closure to azetidinols and ring enlargement to azepinediones. The observed selectivity to exo-alcohol 6 was explained by the conformation of 5 and the best orientation and the availability of the δ-H for the abstraction.
Keywords: homoadamantanes; photoinduced H-abstraction; phthalimides